1996
DOI: 10.1111/j.1476-5381.1996.tb16064.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by propofol of [3H]‐batrachotoxinin‐A 20‐α‐benzoate binding to voltage‐dependent sodium channels in rat cortical synaptosomes

Abstract: 1Propofol (2,6 di-isopropylphenol), an intravenous general anaesthetic, blocks voltage-dependent Na+ channels (Na+ channels). In this study the interaction between propofol and Na+ channels was analysed by examining its effects on neurotoxin binding to various receptor sites of the Na+ channel in rat cerebrocortical synaptosomes. 2 Propofol (10-200,M)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Evidence from isolated nerve terminals suggests that pharmacologically evoked glutamate release is inhibited by volatile anesthetics acting to block presynaptic voltage-gated Na ϩ channels (Ratnakumari and Hemmings, 1996;Ratnakumari et al, 2000;Lingamaneni et al, 2001). Field electrical stimulation of exocytosis in cultured hippocampal neurons depends upon voltage-gated Na ϩ channel function, because it can be blocked by tetrodotoxin, a selective antagonist of neuronal voltage-gated Na ϩ channels that prevents downstream activation of voltage-gated Ca 2ϩ channels for excitation-exocytosis coupling (T. A. Ryan, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from isolated nerve terminals suggests that pharmacologically evoked glutamate release is inhibited by volatile anesthetics acting to block presynaptic voltage-gated Na ϩ channels (Ratnakumari and Hemmings, 1996;Ratnakumari et al, 2000;Lingamaneni et al, 2001). Field electrical stimulation of exocytosis in cultured hippocampal neurons depends upon voltage-gated Na ϩ channel function, because it can be blocked by tetrodotoxin, a selective antagonist of neuronal voltage-gated Na ϩ channels that prevents downstream activation of voltage-gated Ca 2ϩ channels for excitation-exocytosis coupling (T. A. Ryan, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of specifically bound [ 3 H]-BTX-B has served as a facile method to evaluate whether a compound has interaction with site 2 on the sodium channel protein [7]. …”
Section: Methodsmentioning
confidence: 99%
“…More recent studies suggest that propofol effects on Na channels could play a major role in its mechanism of action. Propofol has been shown to displace [ 3 H]-BTX-B binding from sodium channels in rat synaptoneurosomes [7] and inhibit veratridine-evoked sodium influx in rat synaptoneurosomes [8]. In electrophysiology studies, propofol has been shown to inhibit sodium currents from isolated rat neurohypophysial nerve terminals [9].…”
Section: Introductionmentioning
confidence: 99%
“…µM half-maximally inhibited the function of the sodium channel from human brain cortex incorporated into a voltage-clamped planar lipid bilayer [51]. By using a neurochemical approach, Ratnakumari and Hummings [52] reported that propofol (10-200 µM) concentrationdependently inhibited [ 3 H]batrachotoxinin-A 20-α-benzoate binding to sodium channels, with an IC 50 value of 26 µM. In the same study, it was shown that propofol inhibited veratridine-evoked Na + influx with an IC 50 value of 46 µM.…”
Section: Anticonvulsant and Anxiolytic Effectsmentioning
confidence: 99%